MODEL CADANGAN KLAIM UNTUK SISTEM PEMBAYARAN INA-CBGs - Sejahtera, Milla; Khair, Saiful (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
In Indonesia, national health insurance is a social security program for healthprotection, held by Social Security Institution of Health and all Indonesian must beparticipated in it. One of the payment system used to pay claims from health facilities suchas hospital is Indonesia-Case Based Groups (INA-CBGs), i.e. prospective payment systemwhich set from diagnose and procedure grouping, without count its kind and amount ofhealth service provided. This research aims to construct the total loss model for inpatientand outpatient services in hospital using Compound model, where its claim severitymodel constructed from INA-CBGs tariff using simple empirical distribution. This implythat the expected value from claim severity model for this kind of payment system will befixed, unless the tariff is revised. Whereas its frequency claim model constructed fromfrequency of case groups happened in hospital using Poisson distribution as a special caseof Generalized Linear Models (GLM). Its total loss model can be determined usingCompound model and the present value of expected value of total loss    1 PV E t S  willbe the cost reserve that is needed to be prepared by every month. The data used in thisresearch is inpatient and outpatient claim data during 2014 in a D-type hospital in EastNusa Tenggara.